Walsh, Daphne. New Perlican Photograph of a family gathering. - Barrett, Terra (2014)
A family photograph from February 10, 2014 of the following - back row: Ralph Webber, Ruth Peddle, Lillian Hobbs, Eleanor Bristol, Tom Hobbs, Gerald Walsh, Daphne Walsh, Shane Bourdeaux. Front row: Lillian Broomfield, Ronald Peddle, Mariyln Budgell, Mary Peddle, Mary Hobbs, Lavinia Hobbs.